Marketing Strategy For Wadiah Easy Saving BSI Products In The 4.0 Industry Era - Nurul Hidayah; Mila Fursiana Salma Musfiroh Fursiana Salma Musfiroh; Titik Hinawati; Heri Purwanto (AL-ARBAH: Journal of Islamic Finance and Banking, 2021)
AbstractPurpose - This study aims to determine the marketing strategy used in marketing the Easy Wadiah Savings BSI product in the industrial era 4.0.Method - This research is a field research with a qualitative approach. Data collection techniques used are observation, interviews and documentation. The data obtained is then reduced, display data, and draw conclusions.Result - The results of the research at Bank Syariah Indonesia KCP Banjarnegara showed that the marketing strategy used was the 4P (Product, Price, Place, Promotion) marketing mix in marketing the BSI Easy Wadiah Savings product in the industrial era 4.0 which could attract customers to open a BSI Easy Wadiah Savings account. at Bank Syariah Indonesia KCP Banjarnegara so that every month there is an increase. Banks in marketing their products have encouraging and inhibiting factors. There are still many customers who have not followed the development of the industrial era 4.0 so they have not been able to maximize the convenience of the facilities offered by banks.Implication - This research can be used as a reference in marketing Easy Wadiah Savings BSI products in the 4.0 industrial era.Originality - The marketing strategy used in marketing the Easy Wadiah Savings BSI product in the industrial era 4.0 is to utilize the use of the BSI Mobile application to make it easier for customers to open accounts online and perform other banking transactions.